Atypical Alterations of cerebrospinal fluid in Guillain Barré Syndrome: Cases Reports. - Zelada-Ríos, Laura (2021)
Guillain-Barré syndrome shows a cyto-albuminologic dissociation in most patients. Pleocytosis or hypoglycorrhachia may defer the diagnosis, a reason for which an infectious etiology must be ruled out. Three cases of Guillain- Barré are described, whose cerebrospinal fluid tests showed limphocytic pleocytosis and persistently elevated protein concentration, while one of the cases also showed hypoglycorrhachia, and the classic cyto-albuminologic dissociation was only demonstrated in subsequent analysis. The neurophysiologic evaluation revealed an axonal disruption in all the patients. The atypical alterations in the context of acute flaccid paralysis warrant a retesting of the cerebrospinal fluid in order to rule out other etiologies, but without postponing the start of treatment.